A Systematic Review of Sustainable Higher Education Assessment Systems: Indicators, Models, and Future Directions - Mesra, Trisna; Kamil, Insannul; Hadiguna, Rika Ampuh (Jurnal Pendidikan Progresif, 2025)
A Systematic Review of Sustainable Higher Education Assessment System: Indicators, Models, and Future Directions. Objective: Evaluation of the sustainability of higher education institutions (HEIs) has become a major focus in academia, especially as evaluation and ranking systems have evolved into increasingly complex ones. This study aims to provide a set of simple indicators for national policy makers to facilitate the measurement of progress towards sustainability in the higher education sector. Methods: Using a qualitative descriptive approach and a Systematic Literature Review (SLR) method, this study examines 16 types of higher education ranking systems and 16 previous research findings based on the UNEP sustainable higher education framework policy, in order to develop a set of indicators specific to the sustainable higher education sector. Articles were selected using the keywords "sustainable higher education" OR "Sustainable performance measurement" and "Performance indicator AND sustainable HEIs" through a systematic screening process that was in line with the inclusion criteria, including relevance to indicators for assessing sustainable higher education performance. Findings: The results of this study revealed areas that were not yet filled, especially in the criteria that combine all pillars holistically. Previous researchers assessed higher education using only part of the four pillars of sustainability identified by the UN, based on the reviewed literature, it was found that 37.5% of researchers used 3 pillars, 25% of researchers used 2 pillars and 37.5% of researchers used 1 pillar of sustainable higher education. This shows that there is an opportunity for further research that can integrate all aspects of higher education sustainability holistically. This multidimensional approach is important to provide a more complete and comprehensive picture of the performance and contribution of higher education in the context of sustainability. Conclusion: It is necessary to develop a comprehensive and integrative evaluation method, as well as identify performance indicators that measure the impact of interactions between pillars to provide a more comprehensive picture of higher education sustainability. Further research is also needed to bridge the gap in the literature and strengthen the multidimensional approach in assessing sustainable higher education performance. Keywords: model, sustainability indicators, higher education, sustainability.